Analysis of Marketing Communication, Customer Trust, and Customer Loyalty on Telkomsel - Christian Wikanta (Jurnal Strategi Pemasaran, 2018)
Marketing strategy is a way for company to survive from their competitor. One of the way is using promotion activities. The promotion activities can build a company's customer trust in the eyes of consumers and also affect the customer loyalty of a product.This study aim to analyze the influence of marketing communication on customer loyalty through customer trsut of Telkomsel product. This research can be done by spread 100 questionnaires to respondent. The research method is using quantitative analysis and processed with warp PLS program.